2018
DOI: 10.1186/s12889-018-6215-x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic syndrome among adolescents in Dubai, United Arab Emirates, is attributable to the high prevalence of low HDL levels: a cross-sectional study

Abstract: BackgroundMetabolic syndrome (MetS) describes a combination of risk factors that increase the risk of developing chronic diseases. The prevalences of MetS and its risk factors are increasing, especially in the Arab region. A cross-sectional study was carried out to assess the prevalences of MetS and its associated risk factors among adolescents in the United Arab Emirates (UAE).MethodsA total of 596 students (308 boys and 288 girls) aged 10 to 15.9 years old were recruited from 14 public secondary schools in D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
17
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 41 publications
5
17
2
Order By: Relevance
“…Low HDL-c (17%) was the most prevalent MetS component, followed by metabolic glucose (8%), raised TG (5.3%), DBP (1.4%), and high WC (0.5%). Our results are in agreement with several studies reporting HDL as the predominant risk factor among adolescents, followed by high BP, in both Saudi Arabia and the UAE; 45,61,62 with~87% of Saudi children and adolescents aged 10-18 years old had low HDL levels. 61 Moreover, a recent UAE study suggested that if MetS did not account for HDL levels, their prevalence would drop from 3.7% to 0.8%.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Low HDL-c (17%) was the most prevalent MetS component, followed by metabolic glucose (8%), raised TG (5.3%), DBP (1.4%), and high WC (0.5%). Our results are in agreement with several studies reporting HDL as the predominant risk factor among adolescents, followed by high BP, in both Saudi Arabia and the UAE; 45,61,62 with~87% of Saudi children and adolescents aged 10-18 years old had low HDL levels. 61 Moreover, a recent UAE study suggested that if MetS did not account for HDL levels, their prevalence would drop from 3.7% to 0.8%.…”
Section: Discussionsupporting
confidence: 93%
“…44 The prevalence of MetS, according to the IDF criteria, among adolescents aged 10-16 years old attending public schools in Dubai was 3.7%. 45 Similarly, the prevalence of MetS was 3% among Qatari school children, 46 2.3% among Turkish school children aged 10-19 years, 47 and 4.7% in Canadian Tsimshian Nation youth aged 6-18 years. 48 Higher prevalence of 6.3% was reported in another Turkish study in 7-15 years old children 49 and 16.5% among school-aged children in Pakistan based on various definitions.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Co-occurrence of excess body weight and lipid disorders was assessed in many populations, including studies carried out in China, Brazil, Denmark, Germany, USA, Ghana, United Arab Emirates [12][13][14][15][16][17] . Until now, however, no results have been published of similar studies on a large sample of children form a Central or Eastern European country, in which a rapid change of social and economic status of society in the last 30 years has been observed, [18].…”
Section: Introductionmentioning
confidence: 99%